2017
DOI: 10.21037/jgo.2017.06.11
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sarcopenia on outcomes of locally advanced esophageal cancer patients treated with neoadjuvant chemoradiation followed by surgery

Abstract: In our cohort of patients, sarcopenia was associated with a significant increase in acute grade ≥3 toxicity with chemoradiation, suggesting a potential role for neoadjuvant patient selection strategies. There was no difference in pathologic response or overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…Several studies have investigated the effect of sarcopenia on the prognosis of esophageal cancer. However, the results were contradictory [17,18,[20][21][22][23]. In addition, only a few studies included patients who received NACRT instead of chemotherapy as a NAT, and none of these studies demonstrated a significant relationship between sarcopenia and OS [17,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have investigated the effect of sarcopenia on the prognosis of esophageal cancer. However, the results were contradictory [17,18,[20][21][22][23]. In addition, only a few studies included patients who received NACRT instead of chemotherapy as a NAT, and none of these studies demonstrated a significant relationship between sarcopenia and OS [17,23].…”
Section: Discussionmentioning
confidence: 99%
“…However, the results were contradictory [17,18,[20][21][22][23]. In addition, only a few studies included patients who received NACRT instead of chemotherapy as a NAT, and none of these studies demonstrated a significant relationship between sarcopenia and OS [17,23]. Meanwhile, studies on the relationship between the amount of skeletal muscle loss and survival outcomes of esophageal cancer showed relatively consistent results for OS, although they still showed contradictory results for RFS [28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevention and treatment of major complications have remained of paramount significance in improving the outcomes of patients, and the preoperative risk evaluation and clinical intervention are effective measures to prevent the occurrence of major complications. The role of sarcopenia as an effective predictor of postoperative complications has been reported in many clinical studies [51][52][53]. In patients with end-stage liver disease and awaiting transplantation, a model including sarcopenia could even surpass the MELD score in predicting waiting list mortality [54].…”
Section: Discussionmentioning
confidence: 99%
“…Body composition parameters have therefore been increasingly studied in this disease setting as prognostic indicators as well as targets for supportive therapeutic interventions. For instance, several studies have found an association between sarcopenia and increased treatmentrelated toxicities [5,6], resistance to chemoradiotherapy (CRT) [7] and poor outcome [3,8].…”
Section: Introductionmentioning
confidence: 99%